2022
DOI: 10.1186/s13058-022-01529-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomic analysis of primary breast cancer reveals [18F]-fluorodeoxglucose dynamic flux-constants are positively associated with immune pathways and outperform static uptake measures in associating with glucose metabolism

Abstract: Background PET imaging of 18F-fluorodeoxygucose (FDG) is used widely for tumour staging and assessment of treatment response, but the biology associated with FDG uptake is still not fully elucidated. We therefore carried out gene set enrichment analyses (GSEA) of RNA sequencing data to find KEGG pathways associated with FDG uptake in primary breast cancers. Methods Pre-treatment data were analysed from a window-of-opportunity study in which 30 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For instance, the tumor mutational burden risk can be predicted in both primary and liver-metastatic colorectal cancer (AUCs: 0.732 and 0.812) by using radiogenomics analysis based on computed tomography (CT) images ( 57 ). Radiomics features from positron emission tomography (PET) imaging of 18 F-fluorodeoxyglucose (FDG) markedly related to the activation and alteration of mTOR pathway genes in hepatocellular carcinoma ( 58 ), and similar results were also reported in BC that some immune-related pathways were associated with FDG-PET features, such as flux constants and static uptake ( 59 ), and some researchers also aimed to predict Ki-67 status from multiparametric MRI images (AUC: 0.79) in BC ( 60 ). In addition, integration of radiomics and genomic features is also a promising area, such as the radiogenomics model (AUC: 0.87) showed much better performance than the radiomics-only models (AUCs: 0.71 and 0.73) in the prediction of pathological complete response of TNBC ( 61 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, the tumor mutational burden risk can be predicted in both primary and liver-metastatic colorectal cancer (AUCs: 0.732 and 0.812) by using radiogenomics analysis based on computed tomography (CT) images ( 57 ). Radiomics features from positron emission tomography (PET) imaging of 18 F-fluorodeoxyglucose (FDG) markedly related to the activation and alteration of mTOR pathway genes in hepatocellular carcinoma ( 58 ), and similar results were also reported in BC that some immune-related pathways were associated with FDG-PET features, such as flux constants and static uptake ( 59 ), and some researchers also aimed to predict Ki-67 status from multiparametric MRI images (AUC: 0.79) in BC ( 60 ). In addition, integration of radiomics and genomic features is also a promising area, such as the radiogenomics model (AUC: 0.87) showed much better performance than the radiomics-only models (AUCs: 0.71 and 0.73) in the prediction of pathological complete response of TNBC ( 61 ).…”
Section: Discussionmentioning
confidence: 60%
“…Radiogenomics is a promising approach to realizing precision medicine by using non-invasive imaging technology to monitor the molecular behavior of the tumor, as the latest studies reported (56)(57)(58)(59)(60). For instance, the tumor mutational burden risk can be predicted in both primary and livermetastatic colorectal cancer (AUCs: 0.732 and 0.812) by using radiogenomics analysis based on computed tomography (CT) images (57).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 18 F-FDG PET/CT is a non-invasive method to study biochemical and metabolic changes in tumor tissues, which provides useful functional information for identifying surviving tumor tissues [11]. 18 F-FDG metabolic imaging expresses the metabolic level of glucose molecules in the cell [12][13][14]. Tumor cells have increased nucleus division, active cell proliferation, and increased glucose metabolism, which is manifested by increased FDG metabolism and an increased SUV at the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the radiomics signature and GoogLeNet signature were classified into high and low risk groups with median values, and their correlation with different modules was analyzed. Further, the biological significance of the associated modules was analyzed using the Kyoto Gene and Genome Encyclopedia (KEGG) database [ 21 ]. Gene set variation analysis (GSVA) calculated genes of the same significance or function grouped into a single enrichment score in order to assess changes in the activity of the pathway/function in which the genes were located [ 22 ].…”
Section: Methodsmentioning
confidence: 99%